Effect of Networking Based Entrepreneurial Learning on Employability Interest for University Students - Arni, Yusni; Siswandari, Siswandari; Akhyar, Muhammad; Asrowi, Asrowi (Dinamika Pendidikan, 2022)
The study aims at investigating entrepreneurship learning in universities regarding the effect of achievement motivation and creativity on student entrepreneurial intention mediated by online social networks. This study is quantitative research. Data were collected data from 290 online respondents who were students from various private universities in Lampung, South Sumatera and Bangka Belitung provinces in Indonesia. This study using random sampling, and research questionnaires were collected online. The data were analyzed using the structural equation model Smart Pls 3.2.7. This study investigated seven research’hypothesis. The result of the research shows that achievement motivation and creativity have a significant effect on entrepreneurial interest. Itindicates that online social networking can mediate the relationship between achievement motivation and creativity on entrepreneurial interest as well. The findings of this study also contribute to the conceptual framework for lecturers in entrepreneurship learning to increase student entrepreneurship intention. It is recommended to compare the entrepreneurial intention model among state universities as a comparative study to understand how to build entrepreneurial interest in universities as a contribution to create young entrepreneurs.